Does Helping-at-the-Nest Help? The Case of the Acorn Woodpecker - Koenig, Walter D.; Walters, Eric L.; Barve, Sahas (Frontiers in Ecology and Evolution, 2019)
Cooperative breeding groups often involve “helpers-at-the-nest”; indeed, such behavior typically defines this intriguing breeding system. In few cases, however, has it been demonstrated that feeding nestlings by helpers, rather than some other behavior associated with helpers’ presence, leads to greater reproductive success. One prediction of the hypothesis that feeding behavior per se is responsible for the fitness benefits conferred by helpers is that there should be close congruence between the patterns of helping-at-the-nest and the fitness effects of helpers. Here we look for such a relationship in the cooperatively breeding acorn woodpecker (Melanerpes formicivorus) in order to begin to identify the behaviors of helpers that drive the increased fitness benefits they confer. In terms of young fledged, a helper male confers approximately the same fitness benefits to a group as does a helper female; more dramatically, the effects of helper males increases with increasing food supply, most importantly the prior year’s acorn crop on which this species depends, whereas that of helper females does not. These patterns do not match the nest-feeding patterns of helpers, which are greater for females than males and do not increase with a larger acorn crop the prior autumn. In contrast, the proportion of time helpers spend tending acorn-storage facilities (granaries) and are present in or near their home territory is greater for males than females and, at least for males, positively related to the size of the acorn crop. These results fail to support the hypothesis that the primary benefit conferred by helpers is feeding young in the nest; rather, they suggest that behaviors such as territorial defense and predator detection are more important. Understanding exactly what those behaviors are in this, and most other cooperatively breeding systems, remain to be determined.